Evaluasi Implementasi SLiMS menggunakan Model DeLone & McLean terhadap Kualitas Layanan Perpustakaan MTsN 1 Kota Blitar - Arum Wardatul Husna Asyauqiya; Imam Junaris; Zahrotur Roifah (Universitas Nusantara PGRI Kediri, 2026)
The implementation of library automation systems is a crucial strategy for enhancing service quality and management efficiency in the digital era. This study aims to evaluate the success of the Senayan Library Management System (SLiMS) implementation at the Baitul Hikmah Library, MTsN 1 Kota Blitar, using the DeLone & McLean Information Systems Success Model. The research employs a qualitative evaluative case study method, with data collection techniques including in-depth interviews, observation, and documentation studies of 2025 circulation reports. The results indicate that the dimensions of information quality and service quality are primary strengths, with catalog data accuracy reaching 100% and librarians playing a responsive role in technical assistance. Usage data shows high access intensity, with a peak of 5,517 visits in October 2025. While system quality is considered intuitive, challenges were found regarding server stability during peak hours, requiring infrastructure optimization. Overall, the SLiMS implementation has provided net benefits in the form of operational efficiency for staff and increased literacy independence for students, directly enhancing the library's image as a modern information center.